Assessment Barbers Knowledge's and Practice's About Hepatitis Virus In Mosul City - Handay Jabbar Mahmood; Ekhlas Tariq Hassan (College of Nursing,University of Mosul, 2018)
Background and objective: The liver plays an important role and vital that processes nutrients, filters the blood, and fights infections. Irritate or injured in the liver, its function can be affected. Heavy alcohol use, toxins, some medications, and certain medical conditions can cause hepatitis. The study objective is to assess the knowledge's and practice's of barbers about occupational safety Material and methods: Design of the study was cross-sectional descriptive to achieve the objectives of the present study from (17th February 2018) to (30th July 2018). A randomized cross-sectional survey of (60) barber / Mosul City. The sample comprises male and age groups between (15->45) year. The questionnaire which corrects from the expert's opinion, and used the Coefficient Correlation for items which showed that the reliability estimate for the survey was (r = 0.88) that was significant at (P < 0.05) level. Result: The study showed a high percentage of barbers aged between (25 - 35) year (30%). The analysis of data revealed that (53.33%) of barbers hadn't good perception toward their knowledge and showed that (58.33%) of barbers haven't good practices toward their occupational safety. The study founded the significant relationship between demographical data (educational level, marital status and license to practice the profession) and knowledge, also the vital connection between demographical data (license to practice the job) and practices. Conclusion: Our study finds out a marked lower in the information and practices of the barbers working in the Mosul city. Recommendation: Launching health education programs for professionals who are related to individuals in the community. Behavior exchange campaigns for barbers and focuses on them with the aid of occupational safety committees. Key word: Hepatitis, Barbers, Knowledge, Practices.